Influence of the power take-off characteristics on the performance of CECO wave energy converter - M. López (2017)
Previous experimental works proved the ability of CECO to harness wave energy. This wave energyconverter (WEC) is presently at Technology Readiness Level (TRL) three, where characterizing the energyconversion stages and evaluating the energy conversion efficiency is crucial. Therefore, in this workAnsys® Aqwa(r) was applied to study a CECO unit and to obtain a detailed knowledge of its performancethroughout the different energy conversion stages. The numerical model was initially calibrated withresults from experimental tests and then used to simulate different configurations of the power take-off(PTO) system under a wide range of regular and irregular wave conditions. For most of the irregular waveconditions tested, CECO can absorb between 10 and 40% of the incident wave power and transmit to theelectric generator up to 18%. Although the results reveal a high energy conversion efficiency, there is stillscope for improvement of the device by optimizing the PTO. On these grounds, the ideal values of theelectric generator damping coefficient are presented for different wave conditions, which allow to definean adequate control strategy in future works.